Experiences of normalization of pain and injury in elite adolescent basketball - Joncheray, H.; Chavinier-Réla, S.; Burlot, F.; Dalgalarrondo, S.; Fukazawa-Couckuyt, S. (Sociology of Sport Journal, 2023)
The objective of this article was to describe the experiences of normalization of pain and injuries among elite adolescent basketball players and their staff. A total of 10 elite adolescent basketball players, ages 15-17 years and eight members of their staff, were interviewed. Results showed that (a) for both players and staff, being able to normalize pain is considered as a necessity and requires experience; injury is regarded as inevitable and as a way to gain body expertise and (b) technical and medical staffs have difficulties in agreeing on pain and injury management. The originality of the results presented lies in the fact that the elite players interviewed are in training; and that the expectations of the players, the technical staff, and the medical staff were questioned at the same time.